Identifying Frailty Syndrome With Tug Test in Home-Dwelling Elderly - Lidiane Isabel Filippin; Fernanda Miraglia; José Carlos Carvalho Leite; Rafael Chakr; Nathalia Cardoso Oliveira; Dalvana Dutra Berwanger (Brazilian Society of Geriatrics and Gerontology, 2024)
INTRODUCTION: Frailty is an important geriatric syndrome linked to increased mortality, morbidity and the risk of falls Detection of pre-frail and early frail individuals is essential to minimize adverse health outcomes, enabling effective interdisciplinary interventions. OBJECTIVE: To identify frailty syndrome with Timed Up and Go (TUG) test in home-dwelling elderly. METHODS: A home-based cross-sectional study was carried out with 322 elderly people living in a Southern city of Brazil. The Fried frailty criteria was used in order to assess the levels of frailty; the TUG score was investigated as a possible predictor of frailty. The diagnostic ability of different cut-off points for the TUG test was evaluated using the ROC curve. RESULTS: ROC curve analysis for the TUG test, a value of eight seconds was identified as the good cut-off point for the screening of the frailty syndrome. The AUROC was 0.775, with a sensitivity of 85.0%, specificity of 59.5% and negative predictive value of 78.6%. CONCLUSIONS: Considering the limitations of a single test to accomplish the overall complexity of frailty syndrome, in the present study, TUG test was a good screening tool in home-dwelling elderly.